The distinctive features of plastic deformation localization in polycrystalline aluminum by creep; AIP Conference Proceedings; Vol. 1623 : International Conference on Physical Mesomechanics of Multilevel Systems 2014, Tomsk, Russia, 3–5 September 2014 - Orlova D. V. Dina Vladimirovna; Zarikovskaya N. V.; Mirgorodsky S. K. Semen; Danilov V. I. Vladimir Ivanovich; Zuev L. B. Lev (2014, 2014)
Title screen